Characterization and expression analysis of transcription factors in Spartina alterniflora unveil their critical roles in salt stress resistance - Jiang, Yuanyuan; Chen, Shoukun; Gao, Shuqiang; Geng, Jiahui; Shu, Qin; Gao, Shang; Li, Huihui (Frontiers in Plant Science, 2025)
IntroductionTranscription factors (TFs) are essential regulators of gene expression, orchestrating plant growth, development, and responses to environmental stress. Spartina alterniflora, a halophytic species renowned for its exceptional salt resistance, provides an ideal model for investigating the regulatory mechanisms underlying salt tolerance.MethodsHere, we present a comprehensive genome-wide identification and characterization of TFs in S. alterniflora. A total of 5,004 TFs were identified and classified into 56 families, with bHLH, MYB, NAC, and ERF being the most abundant. Gene structure analysis revealed an average of 5.05 exons per TF, with significant variation in exon number, coding sequence length, and GC content across families, reflecting their structural and functional diversity. Evolutionary analysis indicated that S. alterniflora TFs have undergone gene duplication events, with purifying selection (Ka/Ks < 1) shaping their evolution. Tissue-specific expression analysis revealed distinct TF expression patterns across roots, stems, leaves, inflorescences, and seeds, underscoring their roles in organogenesis. Under salt stress, 800 TFs exhibited differential expression, with MYB, bHLH, bZIP, ERF, and NAC families being the most responsive, suggesting their involvement in ion homeostasis, osmoregulation, and antioxidant defense.Results and DiscussionThese findings provide key insights into the transcriptional regulation of salt resistance in S. alterniflora, offering valuable genetic targets for enhancing crop resilience to salinity.